Blood tests to diagnose schizophrenia: self-imposed limits in psychiatry. (October 2020) - Korth, Carsten; Fangerau, Heiner
Summary: The naturalisation of mental disorders—ie, their translation into measurable and preferably molecular variables—has not progressed despite breath-taking discoveries in the neurosciences. We ask whether self-inflicted limits exist among psychiatrists that would prevent them from supporting an imaginary perfect blood test with diagnostic specificity, sensitivity, and validity, which was able to replace clinical diagnosis completely. Although relevant for many mental disorders, we use the clinical disease category schizophrenia here as an example to discuss factors that oppose the naturalisation of clinical disease categories. We defend the provocative position that a complete substitution of the clinical diagnosis by a blood test is generally not desired among clinicians because various factors perpetuate the current diagnostic culture. These are (1) methodological problems, such as a falsely presumed homogeneity of biological causes under the umbrella of one clinical diagnosis that prevents efficient subset identification, (2) professional fears, such as loss of importance of interview-diagnostic expert skills, and (3) conceptual problems, such as a dualistic mindset. We posit that doubts regarding the possibility of a blood test for diagnosing schizophrenia can subtly result in a negative self-fulfilling prophecy, discouraging serious scientific efforts to develop one. We give historical examples of how some of these problems have been solved in other medical disciplines. We predict that only blood tests that improve diagnostic accuracy but do not displace the primacy of clinical diagnosis will be successful. In the future, novel professional expertise for orchestrating various biological variables together with clinical criteria will be needed.